(untitled) (Geologica Macedonica, 2013)
Petrological and geochemical features of the Tertiary magmatic rocks from the Republic of Macedonia were subject of study in this paper. The latest K-Ar, 87Sr/86Sr, and REE data for samples from Kratovo– Zletovo, Sasa–Toranica and Damjan–Buchim ore districts are presented. Whole rock XRF analyses confirmed host rock composition as dacites, quartz-latites, trachyandesites, rhyolites and rhyodacites. Absolute age determinations by the K-Ar dating method have shown ages range from 31 to 14 Ma confirming Oligocene-Miocene age as previously determined by relative methods. Determinations of 87Sr/86Sr ratios (0.70504 to 0.71126) suggest material is sourced from the contact zone between the lower crust and upper mantle where contamination of primary melt occurred. New REE data including negative Eu anomalies along with previously determined La/Yb ratios ranging from 13.3 to 43.0 (Serafimovski 1990) confirm inferred material source. These new data reconfirm previous results, provide insight into the Tertiary magmatic history of the district, and suggest the exact origin of the material that produced the Tertiary magmatic rocks.